2020
DOI: 10.14814/phy2.14620
|View full text |Cite
|
Sign up to set email alerts
|

Loss of membrane integrity drives myofiber death in lipin1‐deficient skeletal muscle

Abstract: Mutations in lipin1 are suggested to be a common cause of massive rhabdomyolysis episodes in children; however, the molecular mechanisms involved in the regulation of myofiber death caused by the absence of lipin1 are not fully understood. Loss of membrane integrity is considered as an effective inducer of cell death in muscular dystrophy. In this study, we utilized a mouse line with selective homozygous lipin1 deficiency in the skeletal muscle (Lipin1 Myf5cKO ) to determine the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 64 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…Our recent publication suggested that lipin1 deficiency alone led to a compromise in muscle membrane integrity and function in skeletal muscle‐specific lipin1 deficient lipin1 Myf5cKO mice (Ramani Sattiraju et al., 2020). EBD, a membrane‐permeable marker, has been widely used to detect membrane damage of skeletal muscle fibres (Matsuda et al., 1995; Straub et al., 1997).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent publication suggested that lipin1 deficiency alone led to a compromise in muscle membrane integrity and function in skeletal muscle‐specific lipin1 deficient lipin1 Myf5cKO mice (Ramani Sattiraju et al., 2020). EBD, a membrane‐permeable marker, has been widely used to detect membrane damage of skeletal muscle fibres (Matsuda et al., 1995; Straub et al., 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In situ muscle force measurements were performed on mice anaesthetized with isoflurane using a SomnoSuite low‐flow anaesthesia system (Kent Scientific, Torrington, CT, USA), as described previously (Myers et al., 2021; Ramani Sattiraju et al., 2020; Wang et al., 2020). Body temperature was monitored with a SomnoSuite temperature probe and maintained at ∼35°C using a heat lamp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EBD dye injection was performed as what we did previously 16 . Briefly, mice were injected with EBD (10mg/ml stock in sterile saline, 0.1ml/10g body weight) I.P.…”
Section: Evans Blue Dye Assaymentioning
confidence: 99%